Actuarial neutrality and financial incentives for early retirement in the Austrian pension system - Dénes Kucsera; Michael Christl (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2016)
This paper studies actuarial neutrality in the Austrian pension system. It is often argued that actuarial neutrality constitutes an incentive for people to retire. We show that there are almost no financial incentives within the Austrian pension corridor, when we use the traditional definition of actuarial neutrality. Taking taxation into account, our results suggest that financial incentives for early retirement stem mainly from the Austrian tax system and not from the pension system itself.
Keywords: J26; H55; 330; actuarial neutrality; early retirement; pension system; retirement